Whose America? : U.S. Immigration Policy since 1980 - Marinari, Maddalena; García, María Cristina, 1960- (Book collections on Project MUSE., 2023)
"A centerpiece of contemporary politics, draconian immigration policies have been long in the making. Maria Cristina Garcia and Maddalena Marinari edit works that examine the post-1980 response of legislation and policy to issues like undocumented immigration, economic shifts, national security, and human rights. Contributors engage with a wide range of ideas, including the effect of the Illegal Immigration Reform and Immigrant Responsibility Act and other laws on the flow of migrants and forms of entry; the impact of neoliberalism and post-Cold War political realignment; the complexities of policing and border enforcement; and the experiences of immigrant groups in communities across the United States. Up-to-date yet rooted in history, Whose America? provides a sophisticated account of recent immigration policy while mapping the ideological struggle to answer an essential question: which people have the right to make America their home or refuge?"--